Is money green? motivations, challenges, and sustainability of selected micro enterprises in Metro Manila - Rizare, Riaanne Jenel (College of Home Economics, University of the Philippines Diliman, 2020)
Industrialization, apart from the economic merit, has brought negative impacts to the environment, particularly pollution. Green businesses are emerging to help diminish this world's environmental problems. The researcher aimed to explore green micro enterprise's motivations, challenges, and perceived sustainability. This study is a qualitative research about 10 green micro enterprises in Metro Manila using a one-to-one in depth semi-structured interview. It aims to discuss the difference between green and non-green products and the perceived strength and weaknesses of a green enterprise, identify the motivations of entrepreneurs in producing and selling green enterprise, identify the motivations of entrepreneurs in producing and selling green products, describe green practices, determine the challenges they currently face, and measure their perceived sustainability in terms of products, raw materials and employment. Results show that majority of the business owners described green product as a product that is less harmful to nature and bulk of them determined that a green enterprise's strength is its benefits to the environment. Their motivations to pursue their enterprise revolved around environmental, personal, social, and financial aspects, with financial motivation being last in their list. Results also show that green micro enterprise owners practice green activities in terms of the selection and use of raw materials, manufacturing and distribution of their products, interaction with their clients, and participation in green seminars and forums. Nevertheless, they still perceive their enterprises as sustainable, considering environmental, social, and economical aspects. The challenges faced by their green micro enterprises, on the other hand, include slow financial growth, difficulty in business management, unsystematic production and high cost pricing, strain in sourcing of materials, costly product distribution, increasing market competition, passive consumer awareness and weak marketing strategies. With these results, it is therefore necessary that green enterprise owners participate more in green seminars in order to improve their knowledge with regards to green products and managing green enterprises. More researches may also be pursued to explore the economic viability and thrivability of the green micro enterprise sector in the market.